2019
DOI: 10.36348/sjnhc.2019.v02i12.003
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation: Application of Kurt Lewin’s Theory on Private Health Care Organizationanl Change

Abstract: An accreditation plan can improve an organizational facilities and services regarding patient care and provides quality improvement skills. In my case scenario, I conceptualized an idea about accreditation of private well-established health care setting. The Kurt Lewin's theory insights a framework of change at the accreditation level, which will be achieved by the application of the transformational leadership style. Transformational leadership style works as guider, motivator, collaborative and bind with sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Another main theme was participation seeking for implementation and executive requirements. These results are similar with a report of hospitals in Australia [16], which shows the importance of stakeholder engagement in the implementation process [17].Regarding the last theme "Implementation, assessment, feedback and stabilization" it is in line with the refreezing step in Kurt Lewin's change theory [18]. The results of the Rechel et al study showed that collecting complete information, stakeholder participation, and getting feedback from them about the decisions made had the greatest impact on the managers' decision-making performance [19].…”
Section: Discussionsupporting
confidence: 91%
“…Another main theme was participation seeking for implementation and executive requirements. These results are similar with a report of hospitals in Australia [16], which shows the importance of stakeholder engagement in the implementation process [17].Regarding the last theme "Implementation, assessment, feedback and stabilization" it is in line with the refreezing step in Kurt Lewin's change theory [18]. The results of the Rechel et al study showed that collecting complete information, stakeholder participation, and getting feedback from them about the decisions made had the greatest impact on the managers' decision-making performance [19].…”
Section: Discussionsupporting
confidence: 91%
“…unfreezing, moving, and refreezing (Burnes et al, 2016;Desmond & Wilson, 2019). Lewin's model is in the form of stages that are tired of being planned in response to a change and improvement that takes place on an ongoing basis that can help a change and improvement that takes place on an ongoing basis that can help the sustainability of an organization (Saleem et al, 2019;Sa'idu, 2021), especially in educational and learning activities in Islamic boarding schools. Therefore, in this case, the researcher seeks to understand the prophetic leadership of Kyai, which has a uniqueness according to the culture of the archipelago in making learning effective in Islamic boarding schools through Kurt Lewin's theory.…”
Section: Introductionmentioning
confidence: 99%
“…Lewin's CMT dictates that change occurs by design, not spontaneously, and occurs in three stages: unfreeze, change, and refreeze (Saleem et al, 2019). Field and force concepts in Lewin's CMT provide a framework for analyzing factors influencing a change, driving or restraining forces.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Lewin's CMT aims to manage change by understanding its process, creating a plan for a smooth transition, and overcoming any anticipated resistance (Saleem et al, 2019). Effective change can occur when the model is applied appropriately and effectively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation